Reactions To Sharia Law Enforcement On Tiktok Account @sahabatsatpollhokseumawe - Fariza, Muhammad Rio (KOMUNIKA, 2024)
The enforcement of Islamic Sharia in Aceh carried out by Wilayatul Hisbah (WH) has attracted public attention, which is spread through TikTok social media content. TikTok has become an effective platform for disseminating this surveillance activity, primarily through the @sahabatsatpollhokseumawe account. This study aims to understand the audience's response to TikTok content related to WH's activities in implementing Islamic Sharia using the Social Judgment Theory (SJT) approach. This study uses a qualitative method with a netnography approach to analyze three posts with the most interactions on the account. Data in the form of audience comments were collected, categorized, and analyzed to identify response patterns, ranging from support and rejection to neutrality. The study results show that audience responses vary, including support for the enforcement of Islamic Sharia, criticism of the implementation method, and curiosity about the legal process applied. In addition, there is debate regarding the privacy of violators whose identities are revealed. This study has practical implications for adjusting WH's digital communication strategy to reach audiences with heterogeneous cultural backgrounds.